Plant protein enrichment effect on the physical, chemical, microbiological, and sensory characteristics of yogurt. Issue 8 (5th July 2022) - Bulut, Menekse; Adal, Eda; Aktar, Tugba
Abstract: Yogurt is a coagulated dairy product that is fermented by typical starter cultures. Yogurt has the highest demand rate among fermented products due to its sensory properties. Well‐consumed food products are being enriched by either adding nutrients or improving the already available content for the development of the product. From this point of view, protein enrichment is one of the approaches that contribute to the nutrient content of food products. The addition of plant‐based protein is a step that improves the nutrient content and is a sustainable approach for the functionalization of the product. In the present study, two types of plant protein were added; chickpea and pea in two different concentrations of 0.5% (w/w) and 1% (w/w) to determine the changes in the physicochemical, textural, microbiological, and sensory properties of the yogurt during storage at 4°C for 21 days. In yogurt samples, pH value, titratable acidity, color measurements ( L *, a *, b *), texture parameters (firmness, consistency, cohesiveness), and microbiological contents show a significant difference during the storage period ( p  < .05). On the other hand, adding plant protein had no significant difference in syneresis value during storage ( p  > .05). The sensory evaluation results highlighted that protein enrichment develops consistency, mouthfeel, and oiliness scores compared to the control product (no plant protein added sample). These significant sensory modalities are determined by the casein network and water‐binding capability of the proteins, which was visible as a result of this study. Novelty impact statement: Plant protein addition improves the sensory properties of yogurt. Plant proteins are effective on the physicochemical properties of fermented dairy products. Functionalization of yogurt is achievable with the usage of plant protein addition.